Paternalistic Leadership Profiles: A Person-Centered Approach. (October 2015) - Chou, Wan-Ju; Sibley, Chris G.; Liu, James H.; Lin, Tzu-Ting; Cheng, Bor-Shiuan
Paternalistic leadership (PL) is a multidimensional construct of three elements that together form a profile model consisting of authoritarianism, benevolence, and morality. Latent profile analysis (LPA) was employed to analyze subordinate response profiles of 1, 146 platoon leaders who rated their company commanders in the Taiwanese military. Results indicated the prevalence of three leadership profiles: most common was a moral-authoritarian leadership profile (60.1%), followed by a moral-benevolent leadership profile (29.1%). Least prevalent was an authoritarian leadership profile (10.8%) low on both morality and benevolence. The probability of subordinate responses fitting in the moral-benevolent leadership profile was associated with greater supervisor identification, more occupational commitment, better task performance, and lower intention to leave; probability of subordinate responses fitting the authoritarian profile was associated with greater intention to leave. There was considerable variability in leadership profile perceptions for the same company commander rated by different subordinates.